Desenvolvimento de sistema de controle híbrido Fuzzy-PID para motogeradores a biogás - Costa, Lucas Ribeiro da (2020)
The use of biogas as a renewable source of energy is already a reality, being applied both in heat production and in power generation and cogeneration plants. In this sense, this work presents itself as a contribution to the strengthening of the use of this renewable energy source, proposing a control system capable of ensuring the quality of the energy generated and satisfactory levels of efficiency. More specifically, a control system was proposed to ensure that the electrical frequency at the generator output remained within the standards required by the Brazilian standard, even under adverse conditions of load variation and fuel composition during the operation of the generator set. For this, a mathematical model was developed in order to represent the mechanical effects of the fuel composition and load variations, as well as to represent the electrical phenomena involved in the conversion of mechanical energy into electrical energy. Then, the model was implemented computationally and tested with a control system composed of a hybrid controller formed by a Fuzzy System that optimizes the gains of PID controllers. Finally, simulations of the proposed system were carried out, contemplating varied operating scenarios, from standard operation in permanent regime to the simulation of defects, serious failures, sudden variations in load and fuel. It was observed that the system without the hybrid controller presents an unstable behavior when submitted to variations of the inputs. With the introduction of the Fuzzy-PID control, it was observed that the system presents a satisfactorily fast response (rise time 0.0094 s and accommodation time 0.0764 s) in addition to ensuring that the oscillations remained within the limit established by norm , with frequency between 59.9 Hz and 60.1 Hz and voltage between 90% and 110% of the nominal value of the electrical network.